Potensi Cangkang Kerang Pensi dan Kulit Udang Sebagai Sumber Kitosan untuk Mengendalikan Penyakit Mosaik pada Tanaman Cabai (Capsicum annuum L.) - Asniwita, Asniwita -; Oktavian, Muhammad Eris; Pebrianti, Herni Dwinta (Universitas Batanghari, 2024)
The mosaic disease caused by the Tobacco mosaic virus (TMV) potentially causes economic losses to chili, so it is necessary to be controlled. One of the ways to control mosaic disease is using chitosan. Chitosan can be obtained from animal shells. The research aims to study the potential of pensi clam shells and shrimp shells as a source of chitosan to control mosaic disease on chili. The research used a Completely Randomized Design with 5 treatments and 5 replications, each experimental unit consist of 3 plants. Treatments included healthy control (without TMV and without chitosan), diseased control (without chitosan), shrimp shell chitosan, pensi clam shell chitosan, and industrial chitosan. Chitosan can delaythe incubation period,the disease severity is reduced by up to 41.86%. Plant height and fruit weight on chitosan protected plants were significantly different from unprotected plants.The height on 28-day old plants with chitosan and without chitosan treatments was 103.39 cm and 95.98 cm respectively, and fruit weight at the first harvest was 57.10 g and 42.57 g respectively. The chitosan used in this research has the potential to reduce mosaic disease in chili. Chitosan can be combined with other control techniques in an integrated disease management.Â Key words: chili, chitosan, mosaic, Tobacco mosaic virus